Equilibrium unemployment, job flows and inflation dynamics - Antonella Trigari (European Central Bank (ECB), 2004)
In order to explain the joint fluctuations of output, inflation and the labor market, this paper first develops a general equilibrium model that integrates a theory of equilibrium unemployment into a monetary model with nominal price rigidities. Then, it estimates a set of structural parameters characterizing the dynamics of the labor market using an application of the minimum distance estimation. The estimated model can explain the cyclical behavior of employment, hours per worker, job creation and job destruction conditional on a shock to monetary policy. Moreover, allowing for variation of the labor input at the extensive margin leads to a significantly lower elasticity of marginal costs with respect to output. This helps to explain the sluggishness of inflation and the persistence of output after a monetary policy shock. The ability of the model to account for the joint dynamics of output and inflation rely on its ability to explain the dynamics in the labor market.
Keywords: E32; J41; J64; E52; E31; 330; business cycles; inflation; monetary policy; Search and Matching Models